2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591964
|View full text |Cite
|
Sign up to set email alerts
|

Split-belt adaptation and gait symmetry in transtibial amputees walking with a hybrid EMG controlled ankle-foot prosthesis

Abstract: Abstract-Our ability to automatically adapt our walking pattern to the demands of our environment is central to maintaining a steady gait. Accordingly, a large effort is being made to extend and integrate this adaptability to lower-limb prostheses. To date, the main focus of this research has been on short term adaptation, such as in response to a terrain transition or a sudden change in the environment. However, long term adaptation and underlying sensorimotor learning processes are critical to optimizing wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The loss of motor control provided through a prosthetic limb may only compound the risk for impaired adaptability. Although literature describing the effect of an amputation on locomotor adaptability is limited, recent studies provide some insight on reactive and adaptive changes when walking is perturbed using a split-belt treadmill[18, 19]. Specifically, one study suggested persons with transtibial amputation (TTA) and those without amputation were equally perturbed at the onset of the unequal walking speeds based on similar magnitude reactive accommodations in step length symmetry[18].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of motor control provided through a prosthetic limb may only compound the risk for impaired adaptability. Although literature describing the effect of an amputation on locomotor adaptability is limited, recent studies provide some insight on reactive and adaptive changes when walking is perturbed using a split-belt treadmill[18, 19]. Specifically, one study suggested persons with transtibial amputation (TTA) and those without amputation were equally perturbed at the onset of the unequal walking speeds based on similar magnitude reactive accommodations in step length symmetry[18].…”
Section: Introductionmentioning
confidence: 99%
“…Gains β SO and β TA could be modified based on the measured GRF peaks ( Figure 4B ) or/and predicted ankle moment peak. This type of control seems more intuitive for the user ( Ortiz-Catalan et al, 2014 ; Kannape and Herr, 2016 ) since it includes a highly adaptive living system in the control of the prosthesis output.…”
Section: Discussionmentioning
confidence: 99%
“…Myoelectric signals with built-in pattern recognition algorithms enable fine motor control in arm prostheses, even without any sensory feedback ( Li et al, 2010 ; Tkach et al, 2014 ). Likewise, it might be possible to improve locomotor outcome measures (e.g., walking symmetry) by controlling a powered prosthesis or orthosis using myoelectric signals from residual or intact muscles ( Sawicki and Ferris, 2009 ; Herr and Grabowski, 2012 ; Takahashi et al, 2015 ; Kannape and Herr, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 Researchers have also investigated locomotor adaptability in patient populations, including patients with cerebral vascular accident, 14 Parkinson's disease, 15 and transtibial amputation. [16][17][18] Patients with transtibial amputation were found to adapt similarly to individuals with no impairment. 17 Split-belt treadmill walking was reported as a rehabilitation intervention to correct temporal-spatial asymmetry in persons following stroke, 14 with benefits retained for at least 3 months.…”
Section: Introductionmentioning
confidence: 99%